Combinatorics : an introduction - Faticoni, Theodore G. (Theodore Gerard), 1954- (Hoboken, New Jersey : Wiley, 2013)
'This book provides a treatment of counting combinatorics that uniquely includes detailed formulas, proofs, and exercises and features coverage of derangements, elementary probability, conditional probability, independent probability, and Bayes' Theorem. Using elementary applications that never advance beyond the use of Venn diagrams, the inclusion/exclusion formula, the multiplication principal, permutations, and combinations, Combinatorics is perfect for courses on discrete or finite mathematics--or as a reference for anyone who wants to learn about the various applications of elementary combinatorics'--
'This book provides a treatment of counting combinatorics and contains topical discussions beyond what is typically seen in other related books. Formulas are discussed and justified, and examples include unique approaches and ideas to the discussed topics'--
Includes bibliographical references (page 309) and index.
Keywords: Combinatorial analysis